CHET TILI GRAMATIKASINI OʻYINLAR ORQALI OʻRGATISH ANNOTATSIYA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article describes the importance of games in learning French grammar. This is important to make teaching grammar concepts easier and more effective for French learners.
Keywords: grammar, French language, technology, comparative analysis, linguistics.